PENERAPAN TEKNIK PEMBELAJARAN CLUSTERING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VII DI SMP YP PGRI 4 MAKASSAR - Heribertus Ruli; Andi Fatmayanti; Ahmad Hasyim (CV. ADIBA AISHA AMIRA, 2023)
This research is classroom action research (CAR) which aims to improve student learning outcomes through Clustering learning techniques for class VIII students of SMP YP PGRI 4. This research is classroom action research with the following stages: planning, implementation, direct evaluation and reflection. The subjects of this study were 30 people, with the research location being at SMP YP PGRI 4 MAKASSAR. The number of cycles in this study were two cycles with the number of meetings in each cycle four times. Data were collected through tests, observations, and documentation which were then analyzed quantitatively and qualitatively. The results of the research in the first cycle showed that the social studies learning outcomes for class VIII had not been completed because students scored >75 only 13 people or 43.3% achieved the standard of completeness, while in the second cycle, there was an increase in learning outcomes where the highest score reached 95 and the score was 95. the lowest was 60. In the first cycle the average student learning outcomes were 66.33 while in the second cycle there was an increase with an average student learning outcome of 78. Thus the use of clustering learning techniques in social studies subjects for class VIII at SMP YP PGRI 4 MAKASSAR can improve student learning outcomes.